DOA NABI INGIN KAYA DAN INGIN MISKIN - Muhammad Mahfud (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2017)
Prayer is a communication tool of human to the God. One of popular prayer in the community is related to the Prophetâ€™s asking to be a poor man, and in the other side the asking to be a rich man. This article discusses the contradiction of the Prophetâ€™s prayer to be a poor man, and in the other side the prayer to be a rich man through TakhrÄ«j al-á¸¤adÄ«th method. The Prophetâ€™s prayers give understanding that the followers should not live with their wealth; however, poor here means simplicity. In other side, the both hadith are á¸aâ€™Ä«f. Keywords: rich, poor, TakhrÄ«j al-á¸¤adÄ«th, makna á¸¥adÄ«th